Effect of pre-partum management on udder and teat development, temperament score, milking traits, milk yield and composition in primiparous Nili-Ravi buffaloes - DAS, KALYAN SUNDAR; SINGH, JITENDRA KUMAR; CHANDRASEKAR, THANGAMALAI (The Indian Journal of Animal Sciences, 2020)
To investigate the effect of pre-partum heifer management on udder and teat development, temperament score, milking traits, milk yield and composition, 12 primiparous Nili-Ravi buffaloes from ICAR-CIRB, Nabha Buffalo Farm were enrolled. All experimental heifers were uniformly divided into 2 groups (6 in each group) based on their duration of pregnancy, dam’s milk yield and body weight. The udders of first group heifers were neither massaged nor they were taken into milking parlour and were considered as control (T0). The udders of other group were massaged for 5–10 min at alternate days since 30 days pre-partum and were considered as treatment (T1) group. The udder/teat biometry, temperament score, milking traits and milk composition of experimental buffaloes were recorded. The T1 group heifers had significantly higher absolute change in udder length, width and depth than control. Though the level of change in teat diameter was significant, it was much more prominent in fore-teats than rear. The massaged group become docile earlier than non-massaged. The milk let-down time was quicker in treatment group than control. The test day milk yield was comparatively higher but the difference was not significant. The milk composition did not vary significantly between T1 and control. It can be concluded that in primiparous Nili- Ravi buffaloes, udder/teat massaging and pre-partum exposure into milking parlour not only helped to develop udder/teat capacity but also reduced fear during milking operations resulting into quick milk let-down/milk flowrate and favoured management during early lactation.